Deep Learning-based PjBL-based Teaching Material Development Training for Strengthening Pancasila Student Profiles in Junior High School Teachers - Suryaningsih, Sri; Arwan, Arwan; Supriyanto, Try; Lestari, Ayu Citra; Rahma, Nuraini (Abdi Masyarakat, 2025)
This community service project was motivated by the low digital literacy and limited capacity of teachers at SMP Negeri 2 Lambu in developing teaching materials based on Project-Based Learning (PjBL) and deep learning pedagogy. The main objective was to empower teachers through training, workshops, and intensive mentoring to enhance their ability to design contextual, innovative learning tools aligned with the Pancasila Student Profile. The methods included pre-test, practice-based training, continuous mentoring, and post-test to evaluate teachers’ competency improvement. The results revealed a significant increase in all indicators: understanding of PjBL concepts rose from 38% to 87%, mastery of deep learning from 25% to 78%, ability to design PjBL lesson plans from 31% to 82%, digital literacy from 28% to 75%, and AI utilization from 12% to 61%. These findings confirm that the program successfully enhanced teachers’ pedagogical capacity and digital literacy while fostering the establishment of a digital learning community to ensure program sustainability.